Descriptions of two new species of Dryinidae from Botswana: Bocchus martellii and Gonatopus martellii (Hymenoptera Chrysidoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two new species of Dryinidae from Botswana are described: Bacchus martellii and Gonatopus martellii.
Keywords: Dryinidae; taxonomy; Bacchus martellii; Gonatopus martellii